Высокоэффективные импульсные электромеханические и электромагнитные устройства уничтожения информации на цифровых накопителях - Болюх, Владимир Федорович; Щукин, Игорь Сергеевич (НТУ "ХПИ", 2015)
Разработан комплекс высокоэффективных автономных импульсных электромеханических и электромагнитных устройств уничтожения информации на цифровых накопителях. Указанные устройства при ограниченных массогабаритных показателях возбуждают мощные механические или магнитные импульсы. Рассмотрены электромеханические устройства индукционно-динамического типа, с аккумулированием механической энергии и устройства комбинированного действия, использующие индукционно-динамические, электродинамические и электромагнитные силы. Предложены конструкции устройств, предназначенных для уничтожения информации на USB флеш-накопителях и твердотельных SSD накопителях. Предложена конструкция импульсного магнитно-механического устройства, в котором уничтожение информации осуществляется механическим и магнитным импульсами одновременно.

It is shown that the most promising way to mechanical destruction of digital information storageis using a pulsed electromechanical and magnetic device and method. The highly efficient autonomous electromechanical and electromagnetic pulse devices destruction of information on digital storage devices are designed. The aim of the paper is the development of designs and advanced technical solutions for highly efficient pulsed electromechanical and magnetic systems of information protection. The excitation source of the inductor is using a capacitive energy storage. This may be implemented by running or the computer turned off for a very short period of time when the signal of unauthorized access. Implement the task can only be provided using mathematical modeling of electromagnetic and mechanical processes, experimental research and development of new technical solutions. These devices with limited weight and overall dimensions excite powerful mechanical or magnetic pulses. Considered electromechanical devices of induction-dynamic type, with accumulation of mechanical energy and the combined action of the device, using an induction-dynamic electrodynamic and electromagnetic forces. Proposed design of devices is intended to destroy information on USB flash drives and solid state drives SSD. The design of pulsed magnetic-mechanical device in which the destruction of information is carried out by mechanical and magnetic pulses simultaneously. Based on the performed works classification of destruction of information devices digital drives is proposed.
High-performance electromechanical and electromagnetic pulse devices for destruction of information on digital drives
Keywords: индуктор; ток электрический; якорь; давление динамическое; аккумулятор